2017
DOI: 10.1002/adbi.201700193
|View full text |Cite
|
Sign up to set email alerts
|

Microsystems for Single‐Cell Analysis

Abstract: Due to the heterogeneity that exists even between cells of the same tissue, it is essential to use techniques and devices able to resolve the characteristics of single biological cells, such as morphology, metabolism, or response to drugs. To that end, different structures with sizes similar to that of individual cells have been developed in recent years, which allow single‐cell studies with high sensitivity and high resolution. By employing a variety of sensing strategies, one can obtain complementary informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 246 publications
0
32
0
Order By: Relevance
“…Swiss‐roll 3D sensors were explored for sensing applications in a microfluidic configuration. For instance, the radial distribution of electric current in the inner channel of the Swiss‐roll architecture allows for the fabrication of highly sensitive impedance based detectors for spectroscopy (Figure c) and tomography applications with sub‐millimeter dimensions . Direct influence of the 3D shape and confinement on biological systems as well as possibilities of cell and tissue manipulation are also investigated using self‐assembled tubular and polygonal shaped structures.…”
Section: Self‐assembled Electronic Devices and Their Shapementioning
confidence: 99%
See 2 more Smart Citations
“…Swiss‐roll 3D sensors were explored for sensing applications in a microfluidic configuration. For instance, the radial distribution of electric current in the inner channel of the Swiss‐roll architecture allows for the fabrication of highly sensitive impedance based detectors for spectroscopy (Figure c) and tomography applications with sub‐millimeter dimensions . Direct influence of the 3D shape and confinement on biological systems as well as possibilities of cell and tissue manipulation are also investigated using self‐assembled tubular and polygonal shaped structures.…”
Section: Self‐assembled Electronic Devices and Their Shapementioning
confidence: 99%
“…On top of these dielectric layers, one can form electrodes for impedance spectroscopy made of a thin Cr adhesion layer and Au conductor deposited by evaporation techniques such as e‐beam evaporation. Rolling is accomplished by the oxidation and dissolution of the Ge sacrificial layer in diluted hydrogen peroxide solution, resulting in arrays of microtubular devices that can be integrated into a PDMS chip for microfluidic applications . Mönch et al applied strain engineering using sputter deposited CuNiMn (100th of nm's) on top of a photoresist to roll up a functional nanomembrane consisting of a magnetic sensor element based on [Py/Cu] 30 multilayers to reveal the giant magnetoresistance (GMR) effect.…”
Section: Self‐assembly Driving Mechanisms and Materials Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological sample can be detected or stimulated using electrodes integrated into the origami structure . The folded structure could conceivably be also patterned with specific magnetic, optical, or biochemical characteristics to target a unique stimulus or measure a selected response of the biosample in‐situ and with high 3D spatiotemporal resolution . Furthermore, the possibility to integrate these microstructures with other microcomponents on‐chip has allowed novel lab‐on‐a‐chip prototypes to enable sensing with high spatial resolution.…”
Section: Origami Biosensorsmentioning
confidence: 99%
“…Ger et al have demonstrated a magnetic origami biosensor self‐assembled by rolling up a magnetic film that actively attracts cells containing diluted magnetite (Fe 3 O 4 ) nanoparticles . Further electrical, photonic, and magnetic features could be potentially integrated on different sections along these rolled‐up microstructures, promoting them as lab‐in‐a‐tube biosensing devices . Elsewhere rolled‐up geometries based on polymers or rolled‐up meshes have been utilized for biosensing.…”
Section: Origami Biosensorsmentioning
confidence: 99%